Gastroprotective Effect of Green Algae Extract (Ulva lactuca L) on Gastric Rats - Wahyu Widyaningsih; Siti Nurasih Afdaliah (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Gastric ulcer is a disease of the digestive tract characterized by mucous damage to secretion of gastric acid and pepsin. One of the potential gastroprotector plants is green algae. The purpose of this study was to examine the gastroprotective effect of ethanol extract of green algae (EEGH) Ulva lactuca L on the gastric of ethanol-induced rats. This study used 36 rats, divided into 6 groups. Group I is a normal group. Group II negative control, ethanol 96% induced. Group III positive control, given comparison of ranitidine dose of 15.75 mg/kgBW. Groups IV, V and VI were given multilevel EEGH, namely 125, 250 and 500 mg/kgBW. The treatment was carried out for 14 days, on the 14th day ethanol 96% was induced and then dissected. Research data on gastric ulcer index and protection ratio were analyzed using One Way ANOVA with a confidence level of 95%. The results of the EEGH statistical test dose of 500 mg/kgBW with negative controls showed a significant difference with p value of 0.013 (p<0.05). The EEGH 500 mg/kgBW has the ability as an effective gastroprotector, as seen from the gastric ulcer index value of 0.5 and the protection ratio of 78.94%.Keywords: Ethanol, gastroprotector, protection ratio, ulcer index, Ulva lactuca L.78,94%.